WHITHER INDONESIA’S ISLAMIC MODERATISM? A Reexamination on the Moderate Vision of Muhammadiyah and NU (State Islamic University (UIN) of Sunan Ampel Surabaya, 2013)
This paper seeks to analyze the moderate ideology of Muhammadiyah dan NU, popularly known as the champion of Indonesia’s moderate Islam. Questions to be investigated are: to what extent that NU and Muhammadiyah theologically represent moderatism? Is there any such thing as “moderate Islam” in Indonesia? How can a blue-print of moderate Islam be formulated in the context of Indonesian Islam? The underpinning theoretical assumption upon which this paper is based is that the theological formulation of Islamic moderatism developed by NU and Muhammadiyah can no longer accommodate the latest challenges and demands of the era. In the context of Indonesian Islam, therefore, a representative formulation of how moderate Islam can be constructed is badly needed. What NU and Muhammadiyah have demonstrated so far in the landscape of Indonesian Islam, nevertheless, can serve as a stepping stone towards building a more liable formulation of an Indonesian Islam in the future.